ATL: Does Metabolic Response Predicts Survival?. Issue 2 (1st February 2014) - Dhull, Varun Singh; Sharma, Punit; Sharma, Daya Nand; Maharjan, Sagar; Suman KC, Sudhir; Patel, Chetan; Bal, Chandrasekhar; Kumar, Rakesh
Abstract : Purpose: This study aimed to assess the role of 18 F-fluorodeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG PET-CT) in response assessment of patients with recurrent carcinoma cervix and in evaluating the predictive value of metabolic response for progression-free survival (PFS) and overall survival (OS). Methods: Thirty-six patients with histopathologically or clinically evident recurrent cervical carcinoma underwent a pretherapy and a posttherapy 18 F-FDG PET-CT for treatment response evaluation. Positron emission tomography–CT images were analyzed by 2 experienced nuclear medicine physicians. Response was categorized using European Organization for Research and Treatment of Cancer (EORTC) criteria into complete metabolic response (CMR), partial metabolic response (PMR), stable metabolic disease (SMD), and progressive metabolic disease (PMD). Clinical/imaging follow-up (minimum of 6 months) and/or histopathologic findings were taken as reference standard. Patients were categorized into 2 groups, those with PMD and those without PMD (ie, CMR, PMR, and SMD). Progression-free survival and OS based on PET-CT response were measured from the date of posttherapy PET-CT to the first documentation of progression of disease and death, respectively. Results: On the basis of metabolic response on posttherapy PET-CT, 6 patients had CMR, 12 patients had PMR, 7 patients had SMD, and 11 patients had PMD. Progression-free survival for patients with cervical carcinoma ranged from 0.5 to 26.5 months (mean [SD], 6.7 [6.1] months). Median PFS for patients with PMD was 3.1 months, whereas median PFS for those without PMD was not reached. Patients who did not show PMD on posttherapy PET-CT had a significantly better PFS than those patients who showed PMD ( P < 0.0001; HR, 0.14). There was no statistically significant difference in OS between the 2 groups ( P = 0.187; HR, 0.39). Conclusions: 18 F-fluorodeoxyglucose PET-CT is an effective tool for treatment response evaluation in recurrent carcinoma cervix. Patients with metabolically progressive disease on posttherapy 18 F-FDG PET-CT have a significantly shorter PFS.